Willingness to pay for rapid diagnostic tests for the diagnosis and treatment of malaria in southeast Nigeria: ex post and ex ante - Uguru Nkoli P; Onwujekwe Obinna E; Uzochukwu Benjamin SC; Ughasoro Maduka D; Ezeoke Ogochukwu P (BMC, 2010)
Abstract Background The introduction of rapid diagnostic tests (RDTs) has improved the diagnosis and treatment of malaria. However, any successful control of malaria will depend on socio-economic factors that influence its management in the community. Willingness to pay (WTP) is important because consumer responses to prices will influence utilization of services and revenues collected. Also the consumer's attitude can influence monetary valuation with respect to different conditions ex post and ex ante. Methods WTP for RDT for Malaria was assessed by the contingent valuation method using a bidding game approach in rural and urban communities in southeast Nigeria. The ex post WTP was assessed at the health centers on 618 patients immediately following diagnosis of malaria with RDT and the ex ante WTP was assessed by household interviews on 1020 householders with a prior history of malaria. Results For the ex ante WTP, 51% of the respondents in urban and 24.7% in rural areas were willing to pay for RDT. The mean WTP (235.49 naira) in urban is higher than WTP (182.05 Naira) in rural areas. For the ex post WTP, 89 and 90.7% of the respondents in urban and rural areas respectively were WTP. The mean WTP (372.30 naira) in urban is also higher than (296.28 naira) in rural areas. For the ex post scenario, the lower two Social Economic Status (SES) quartiles were more willing to pay and the mean WTP is higher than the higher two SES while in the ex ante scenario, the higher two SES quartiles were more WTP and with a higher WTP than the lower two SES quartile. Ex ante and ex post WTP were directly dependent on costs. Conclusion The ex post WTP is higher than the ex ante WTP and both are greater than the current cost of RDTs. Urban dwellers were more willing to pay than the rural dwellers. The mean WTP should be considered when designing suitable financial strategies for making RDTs available to communities.